Effect of power and frequency of ultrasonic energy towards diesel separation from sand: article / Mohammad Fitri Abu Bakar, Muhammad Shafiq Mat Shayuti - Abu Bakar, Mohammad Fitri; Mat Shayuti, Muhammad Shafiq (2019)
Produced sand is considered as one of major problems during the production of petroleum. When produced sand rise up from the well into the separator, it actually contains some crude oil in it. Produced sand cannot be disposed without proper treatment. Known as ultrasonic separation technique, it is a method for separating the crude oil from the produced sand and at the same time treating the oil sand so that it can be disposed into the environment without harming it. This experiment tests the efficiency of ultrasonic cleaning technique towards different sand weight (10g, 20g, and 30g), different cleaning time (30 minutes and 45 minutes) and also different diesel volume (1.5 ml and 2.5 ml) as well as to see the effect of ultrasonic power towards the morphology of sand after the separation process. By fixing the input of ultrasonic energy to 68 kHz and the power input to 100 watt, the results for the three tests were recorded and the separation percentage obtained from 10g, 20g and 30g sand weight for 30 minutes are 86.57%, 85.84%, and 84.97% respectively. Meanwhile for the test of 45 minutes for the same sand weight, the results obtained are 96.34%, 92.87%, and 90.75% respectively. Results shown that the efficiency of ultrasonic energy affected by the sand weight, cleaning time, and volume of diesel. Also, the size of sand grain before and after separation process was observed and the size of sand grain does decrease due to the effect of ultrasonic energy where it produce bubble which produced and collapsed during the separation process.